An unusual case of dilated coronary sinus: case report and clinical implications. Issue 10 (9th October 2021) - Cardi, Thomas; Ohana, Mickaël; Marzak, Halim; Jesel, Laurence
Abstract: Background : The presence of a dilated coronary sinus (CS) assessed by transthoracic echocardiography (TTE) is highly suggestive of inferior or superior vena cava (SVC) anomalies, in the absence of a shunt. The most frequent finding is the persistence of a left superior vena cava (LSVC): well-known feature to electrophysiologists. Abnormal inferior vena cava (IVC) drainage is another cause of CS dilatation. Case summary : An 83-year-old woman presented with heart failure symptoms, atrial fibrillation with rapid ventricular rate, and a dilated CS assessed by TTE. Atrioventricular (AV) node ablation was considered given the poor efficacy of a rate control strategy. Cardiac computed tomography (CT) revealed a double SVC with an LSVC draining directly into the dilated CS. Single-lead pacemaker implantation was performed using a right-sided vascular access with no technical difficulties. An aborted AV node ablation procedure was due to the impossibility of getting to the right atrium. Fluoroscopy and CT imaging at second look analysis confirmed the diagnosis of an abnormal IVC with an agenesia of its supra-hepatic segment directly drained into the CS. Discussion : Our clinical case illustrates an unusual and rare double venous abnormality: both LSVC and IVC directly drained into the CS and were responsible for its massive dilatation.